2016
DOI: 10.11606/issn.2238-6149.v27i1p42-51
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação transcultural e reprodutibilidade do Measure of the Quality of the Enviroment em indivíduos com hemiparesia

Abstract: A funcionalidade sofre a influência de aspectos relacionados à condição de saúde, bem como de fatores ambientais. Dentre os questionários que mensuram o impacto de fatores ambientais na funcionalidade, o Measure of the Quality of the Environment (MQE) é comumente utilizado. O objetivo deste estudo foi adaptar transculturalmente o MQE para o português-Brasil e avaliar sua reprodutibilidade. Após adaptação transcultural, o MQE foi aplicado em 28 indivíduos pós-AVE, duas vezes, com intervalo de sete a 10 dias. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
1
6
0
8
Order By: Relevance
“…Two participants had particularly high differences in their mean scores between the first and second test occasions and were considered outliers. 13,29 Thus, similar to previous studies, 13,29 the analysis of the test-retest reliability was reported for the entire sample (n = 31) and without the two outliers (n = 29). The test-retest assessments were carried-out 5 to 7 days apart, which can be considered a short period of time for changes in locomotion ability to occur.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Two participants had particularly high differences in their mean scores between the first and second test occasions and were considered outliers. 13,29 Thus, similar to previous studies, 13,29 the analysis of the test-retest reliability was reported for the entire sample (n = 31) and without the two outliers (n = 29). The test-retest assessments were carried-out 5 to 7 days apart, which can be considered a short period of time for changes in locomotion ability to occur.…”
Section: Discussionsupporting
confidence: 74%
“…The Bland‐Altman plot revealed that the participants showed a homogeneous distribution in scores around the mean. Two participants had particularly high differences in their mean scores between the first and second test occasions and were considered outliers . Thus, similar to previous studies, the analysis of the test‐retest reliability was reported for the entire sample (n = 31) and without the two outliers (n = 29).…”
Section: Discussionmentioning
confidence: 57%
“…Este acréscimo visou facilitar a interpretação do item por aqueles indivíduos que apresentem dificuldades para estimar distâncias, ampliando desta forma a possibilidade de compreensão do item. Durante o processo de adaptação transcultural é recomendado que o instrumento seja aplicado em uma população alvo de no mínimo de cinco indivíduos 13 , a fim de avaliar a compreensão da versão pré final 21,22 . Neste estágio, a mGES-Brasil foi aplicada em 12 indivíduos, sendo que nenhum participante apresentou qualquer dificuldade de compreensão, o que demonstra ausência de problemas quanto a redação e clareza dos itens.…”
Section: Discussionunclassified
“…Os domínios do MQE são: atitudes e suporte social; trabalho e renda; serviços governamentais e públicos; igualdade de oportunidade; orientações políticas, referentes ao ambiente social; por fim estrutura física e acessibilidade e tecnologia, referentes ao ambiente físico. 21 A vantagem de se utilizar a versão curta do instrumento é pela objetividade, com rápida aplicação e fácil interpretação dos escores. A versão curta do MQE já foi testada em indivíduos com AVC, foi traduzida, validada e demonstrou boa reprodutibilidade.…”
Section: Fatores Ambientais: Measure Of the Quality Of Environment (Mqe)unclassified